Structural interaction and functional regulation of polycystin-2 by filamin - Wang, Qian (2012)
Filamins are important actin cross-linking proteins implicated in scaffolding, membrane stabilization and signal transduction, through interaction with ion channels, receptors and signaling proteins. Here we report the physical and functional interaction between filamins and polycystin-2, a TRP-type cation channel mutated in 10-15% patients with autosomal dominant polycystic kidney disease. Yeast two-hybrid and GST pull-down experiments demonstrated that the C-termini of filamin isoforms A, B and C directly bind to both the intracellular N- and C-termini of polycystin-2. Reciprocal co-immunoprecipitation experiments showed that endogenous polycystin-2 and filamins are in the same complexes in renal epithelial cells and human melanoma A7 cells. We then examined the effect of filamin on polycystin-2 channel function by electrophysiology studies with a lipid bilayer reconstitution system and found that filamin-A substantially inhibits polycystin-2 channel activity. Our study indicates that filamins are important regulators of polycystin-2 channel function, and further links actin cytoskeletal dynamics to the regulation of this channel protein. © 2012 Wang et al.